(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
The paper is concerned with arguing the existence of a relationship between the enactive theory of perception and aesthetics. One of the leading figures in the theory of enactment, Alva Noe, pointed out that the works of art constitute one of the keys to understand how perception and cognition realize their enactment onto reality. Art objects are, in fact, a very peculiar case of artefacts since they are considered as being able to quicken the living beings’ organization in their interaction to the world. Do they create a different atmosphere? Do they “furnish” the surrounding habitat with new meanings? The paper argues that these are, of course, fundamental elements in the art’s action onto reality. As far as the subjective enactment of perception is concerned, together with power in designing life organization, art has arguably another original functions, that of building new “environs” where experience can meet reality under a different light and thus prepare the field for other creative contributions, both cultural and technological.